A framework to estimate the large-scale impacts of energy community roll-out. Issue 7 (July 2022) - Fina, Bernadette; Monsberger, Carolin; Auer, Hans
Abstract: The gradual enactment of legislation for energy communities in individual European countries has increased the public awareness of these novel concepts. While the establishment of individual, isolated energy communities is unlikely to have any far-reaching effects, it is presumed that the large-scale roll-out will indeed significantly impact different stakeholders. Since the diffusion of energy communities is expected to gain momentum within the next years, this study aims to provide a framework to assess the impact of a large-scale roll-out of solar-PV based energy communities. This nine-step framework provides guidance for determining the number of buildings per type and roof tilt, assessing the usable rooftop area for PV installation and realistically installed PV capacities, estimating the number of future residential PV systems based on renewable expansion plans, determining the shares of buildings to be equipped with PV systems, setting up model energy communities, and upscaling. The nine-step framework is not only described theoretically but also applied to Austria as a case study. Thereby, specific focus is put on Austria's rural areas and thus the single-family building stock. Results indicate the impact of a large-scale roll-out of renewable energy communities on participants' electricity bills, electricity suppliers' sales, and grid operators revenues due to reduced grid tariffs for inner-community electricity transfer. The ability to determine the future impacts of energy community roll-out supports stakeholders in their proper planning towards an energy landscape that includes energy communities. Abstract : Framework to estimate energy community impact; Energy community roll-out; Renewable energy communities; PV electricity sharing; Settlement patterns; Austria